2003
DOI: 10.1021/jp030278o
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous Analysis of Reversible Faradaic Depolarization Processes in the Electrokinetics of the Metal/Electrolyte Solution Interface

Abstract: The bipolar faradaic depolarization of the interface metal/solution is examined for the situation in which the transversal electron transfer is limited by mass transfer of the components of a reversible redox couple. Transversal diffusion of the electroactive species to and from the surface and lateral convective mass transport, resulting from a pressure gradient applied along the surface, are taken into account. The analysis first focuses on the case in which the lateral electric field required for bipolar be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(107 citation statements)
references
References 16 publications
(42 reference statements)
9
98
0
Order By: Relevance
“…(The system then resembles two electrochemical cells in series.) Under direct current conditions, Duval et al [97,98,99,100] have shown that Faradaic reactions with a known redox couple can alter the electrokinetic 11 response of the metal surface, and the groups of Crooks and Tallerek [101,102,103] have shown how water and buffer reactions can lead to electric field gradient focusing of charged analytes, due to the spatially dependent electrophoretic velocity near the bipolar electrode. It would be interesting to extend the models in these papers to include diffuse-layer effects on reaction rates (the generalized Frumkin correction to the Butler-Volmer equation [104,105]) and apply them to AC forcing of the bipolar electrode with a DC bias, or other examples of ICEO phenomena described above.…”
Section: Electrochemical Kineticsmentioning
confidence: 99%
“…(The system then resembles two electrochemical cells in series.) Under direct current conditions, Duval et al [97,98,99,100] have shown that Faradaic reactions with a known redox couple can alter the electrokinetic 11 response of the metal surface, and the groups of Crooks and Tallerek [101,102,103] have shown how water and buffer reactions can lead to electric field gradient focusing of charged analytes, due to the spatially dependent electrophoretic velocity near the bipolar electrode. It would be interesting to extend the models in these papers to include diffuse-layer effects on reaction rates (the generalized Frumkin correction to the Butler-Volmer equation [104,105]) and apply them to AC forcing of the bipolar electrode with a DC bias, or other examples of ICEO phenomena described above.…”
Section: Electrochemical Kineticsmentioning
confidence: 99%
“…Calculation of the corresponding zeta-potential may be performed using the classical linear Helmholtz-Smoluchowski (H-S) equation [22][23][24][25]. If the solution between the two conducting surfaces contains a redox couple, and a lateral potential is either externally applied in the solution across the cell [26] or generated by tangential hydrodynamic flow [12,19], faradaic depolarization takes place. The potential distribution in the thin solution layer adjacent to the surfaces leads to reduction of Ox at one side of the surface and oxidation of R at the other.…”
Section: Reversible Faradaic Depolarization In Electrokinetics: Nonlimentioning
confidence: 99%
“…The steady state streaming current, generated upon application of a pressure gradient P , is balanced by the countercurrent, which now contains an electronic contribution. The resulting streaming potential ϕ str is defined by the H-S equation, extended with a bipolar conductance term [19] ε 0 ε r ζ P η…”
Section: Reversible Faradaic Depolarization In Electrokinetics: Nonlimentioning
confidence: 99%
See 2 more Smart Citations